Studi Kasus Pengaruh Perbedaan Spesifikasi Fuel Gas terhadap Kinerja Pembakaran Thermal Oxidizer Unit di PT X - Muhammad Fiqih Alif Utama; Ratni Dewi; Sariadi Sariadi (Politeknik Negeri Lhokseumawe, 2023)
Fuel gas is a term used by the industry to refer to fuel in physical form or gas form. The type of fuel used in the thermal oxidizer at the Sulfur Recovery Unit (SRU) plant is fuel gas. The thermal oxidizer is a device that functions to oxidize residual H2S, elemental sulfur, and CO2 derived from the sour gas purification process. Currently, the reliability of the thermal oxidizer in operation needs special attention by management and the operations team because the ability of the refractory in the Thermal Oxidizer unit to maintain combustion heat is not optimal and stable so the combustion heat has touched the thermal oxidizer at several points to cause cracks and leaks. The purpose of this study is to analyze the effect of differences in fuel gas specifications on combustion performance and heat energy formed in the thermal oxidizer unit, to analyze the effect of differences in fuel gas specifications on increasing the operating temperature and reliability of the thermal oxidizer and to analyze the impact of the risk of implementing different gas usage on operations at the SRU plant. The method used in the research is causal comparative where observations are made of data from factors that are thought to be the cause as a comparison of differences in the use of fuel gas. In this study LP fuel gas is the best fuel usage option because it is more efficient and controlling the risk level can be done optimally with the use of LP fuel gas.